If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-12=x/4+4
We move all terms to the left:
-12-(x/4+4)=0
We get rid of parentheses
-x/4-4-12=0
We multiply all the terms by the denominator
-x-4*4-12*4=0
We add all the numbers together, and all the variables
-1x-64=0
We move all terms containing x to the left, all other terms to the right
-x=64
x=64/-1
x=-64
| 3z/8+6=4 | | x/5x-4=4x | | 9y-8=8=9y | | x9-2=0 | | 18s=126 | | 6(-r+6)=18 | | 54=7y+2y | | Q=150-2x | | (x-5)/x=4/9 | | -12x+3(2x-5)=-20-5x | | 65=5/9(f-32) | | 6x-6x=6-6 | | (x-8)3x=180 | | 42=7(z=3) | | 2e+4e=15 | | b(20)+2b(15)=220 | | 128=9x-5x+32 | | 2(3w+4)=38 | | b(.20)+2b(.15)=2.20 | | -3(6-5b)=6b+36 | | 8/9=4/3x | | 3p3=21p | | -5x-1.5=1.8 | | 3y+30=7y-10 | | 2x+1/x-1=3/5 | | 2x+42=11x-18 | | y/4-6=2y-20 | | (y+1)=0 | | 6=4(x-4)+4 | | x2+10x+8=x | | 6(x+2)-x=4(x-4)+4 | | 14=n/5+6 |